The Registration Policy of Interfaith Marriage Overseas for Indonesian Citizen - Sri Wahyuni; Resti Dian Luthviati; Muhammad Jihadul Hayat; Utkarsh K. Mishra (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2022)
Interfaith marriages have long been a debated issue of marriage law in Indonesia. Since the marriage law was issued, there has been no clear legal stance governing interfaith marriage, particularly when involve Muslim/ah bride or groom. While the fact is, interfaith marriage is an unstoppable reality in the plural society. Not being recognized for its legitimacy according to Indonesian regulation makes the interfaith couples think to utilize out of the box solution that is conducting marriage overseas. The problem is whether interfaith marriages abroad can be considered legal in Indonesia and how is the registration process in Indonesia after their arrival. This study aims to explain the process of registering interfaith marriages carried out outside Indonesia after the couples return to Indonesia. The data was collected through the study of primary legal materials of Indonesian marriage laws and lower regulations. Data were also collected through interviews. This article argues that interfaith marriages are not well regulated in Indonesia. Therefore their validity cannot be justified. Interfaith marriages conducted abroad can be registered at the civil registry office. The civil registry office does not question the validity of the marriage.